Primary tuberculosis of maxillary sinus - A rare case report - Seema Patil; A Latha Shree; B V Subhash; R Shriyanka (Wolters Kluwer Medknow Publications, 2023)
Tuberculosis of the maxillary sinus is uncommon. Primary tuberculosis involving the sinus is very rare, and it is generally secondary to pulmonary involvement. The clinical presentation of this condition is vague and not pathognomonic. This may result in an incorrect diagnosis leading to complications. An unusual presentation of primary tuberculosis affecting the maxillary sinus in a 54-year-old male is discussed in the present case report.